A QUANTUM CHEMICAL STUDY ON ELUCIDATION OF MOLECULAR STRUCTURE, ELECTRIC MOMENTS AND VIBRATIONAL ANALYSES OF BETA-DAMASCENONE AND ITS ISOMER- A COMPARATIVE STUDY - Kumar, Amarendra (International Journal of Engineering Technologies and Management Research, 2017)
A comparative, quantum chemical study on of energies, dipole moment and vibrational wavenumbers of trans- beta-Damascenone and cis-beta-Damscenone was carried out by using B3LYP methods with 6-311+G(d,p) and 6-311++G(d,p) basis sets. A complete vibrational analysis of both the compounds has been performed and assignments are made on the basis of potential energy distribution. The frontier orbitals and molecular electrostatic potential surface study has also been employed to understand the active sites of title compounds. The calculation of the IR spectra is not only important in order to confirm the validity of the simulations but it also allows additional insight into the molecular level of the system not accessible from experiment. Therefore, simulated IR and Raman spectra of the title compounds are also presented in this study. The structure activity relationship based on the study of frontier orbital gap, dipole moment data along with the molecular electrostatic potential map of the title compounds have been used to understand the active sites of the molecules.